BENCANA SOSIAL KASUS LUMPUR PT. LAPINDO BRANTAS SIDOARJO, JAWA TIMUR - ELMAGHFIRA PUTRI ELIKA; RISNA RESNAWATY; ARIE SURYA GUTAMA (Universitas Padjadjaran, 2017)
This article explores the Lapindo Case not only as a physical disaster, but as a social disaster. The incident occured has threatened the people of Porong, Sidoarjo and also hit the East Java’s economics and affected to the Indonesian development programs. There are not much articles in social science perspectives about this tragedy. This article is constructed Based on some of the information obtained, Sidoarjo in order to explore the, both high and low, political-economy aspects of the Lapindo Case. The author found that the destroyed public spaces, because of mudflow, had caused the damages of social sphe res, which lead to a serious social-political disaster. These facts has lead to multidimensional responses of the elite (the high politics) and the people (the low politics).